PdPt bimetallic nanowires with efficient oxidase mimic activity for the colorimetric detection of acid phosphatase in acidic media. Issue 29 (5th July 2019) - Jin, Lihua; Sun, Yanan; Shi, Lulu; Li, Cong; Shen, Yehua
Abstract : PdPt bimetallic alloy nanowires (Pd/Pt NWs) were found to exhibit excellent oxidase-like activity and can be applied to sensitively detect the activity of acid phosphatase (ACP) in acidic media. Abstract : In this study, we found that PdPt bimetallic alloy nanowires (Pd/Pt NWs) exhibited excellent oxidase-like activity in acidic media. Their oxidase-like activity could be readily tailored by a well-defined Pd/Pt ratio, while the nanowires with Pd/Pt ratio of 1 : 3 (defined as Pd/Pt-1 : 3 NWs) proved to exhibit the most efficient catalytic oxidation activity. By using their excellent oxidase-like activity, we developed a simple colorimetric assay to detect the activity of acid phosphatase (ACP) based on its catalytic hydrolysate, ascorbic acid (AA), which effectively inhibited the action of the Pd/Pt-1 : 3 NW-mediated TMB-oxidized chromogenic reaction. Good linearity between the absorbance change and activity of ACP was obtained in the range of 0.17–2.67 U L −1, with the limit of detection as low as 0.06 U L −1 . Moreover, the proposed method was also adopted to determine the ACP activity in mimicking physiological sample solutions with satisfactory results, illustrating its great potential for biological analysis.